It's a Marathon, Not a Sprint: Rapid Evaluation of CBME Program Implementation. (15th October 2019) - Hall, Andrew K.; Rich, Jessica; Dagnone, J. Damon; Weersink, Kristen; Caudle, Jaelyn; Sherbino, Jonathan; Frank, Jason R.; Bandiera, Glen; Van Melle, Elaine
Abstract : Purpose: Despite the broad endorsement of competency-based medical education (CBME), myriad difficulties have arisen in program implementation. The authors sought to evaluate the fidelity of implementation and identify early outcomes of CBME implementation using Rapid Evaluation to facilitate transformative change. Method: Case-study methodology was used to explore the lived experience of implementing CBME in the emergency medicine postgraduate program at Queen's University, Canada, using iterative cycles of Rapid Evaluation in 2017–2018. After the intended implementation was explicitly described, stakeholder focus groups and interviews were conducted at 3 and 9 months post-implementation to evaluate the fidelity of implementation and early outcomes. Analyses were abductive, using the CBME core components framework and data-driven approaches to understand stakeholders' experiences. Results: In comparing planned with enacted implementation, important themes emerged with resultant opportunities for adaption. For example, lack of a shared mental model resulted in frontline difficulty with assessment and feedback, and a concern that the granularity of competency-focused assessment may result in "missing the forest for the trees, " prompting the return of global assessment. Resident engagement in personal learning plans was not uniformly adopted and learning experiences tailored to residents' needs were slow to follow. Conclusions: Rapid Evaluation provided critical insights into the successes and challenges of operationalization of CBME. Implementing the practical components of CBME was perceived as a sprint, while realizing the principles of CBME and changing culture in postgraduate training is a marathon requiring sustained effort in the form of frequent evaluation and continuous faculty and resident development.